Infantile Epileptic Encephalopathy of Ohtahara - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1998)
A case of infantile epileptic encephalopathy (Ohtahara syndrome) with EEG suppression-bursts at 2 days and associated with diffuse cerebral migrational and maturation disorder, diagnosed at autopsy at 19 months, is reported from Montreal Children's Hospital, McGill University, Montreal, Canada.